Information and communication technologies in tourism 2013 : proceedings of the International Conference in Innsbruck, Austria, January 22-25, 2013 - International Conference on Information Communication Technologies in Health; Cantoni, Lorenzo.; Xiang, Zheng. (Springer, 2013)
The papers presented in this volume advance the state of the art in social media and Web 2.0, electronic tourism marketing, web site and search engine optimization, technology adoption and diffusion, online communities, tourism management and decision support, eLearning, mobile technologies and applications in tourism, recommender systems, e-intermediaries and networks in tourism, customer research in e-tourism and user generated content. The volume collects research papers of prominent scholars from around the world with a disciplinary background in the fields of social or computer sciences. The book covers the most significant topics within the study field of electronic tourism and addresses both, academics and practitioners interested in the latest advances in the electronic travel and tourism domain.